Quality function deployment and sensitivity analysis of requirements for future aircraft propulsion cryogenic cooling systems - Palmer, Joe; Shehab, Essam; Fan, Ip-Shing; Husband, Mark (Cranfield University Press, 2013)
A number of novel future airframe and propulsion concepts are considered in order to meet aviation targets set by various aviation regulatory bodies including NASA and the Advisory Council for Aeronautics Research in Europe (ACARE). The current NASA concept for long-range civil aircraft is the Blended-Wing Body (BWB) aircraft, coupled with turbo-electric distributed propulsion (TeDP), to enable a host of efficiency benefits over current designs. NASA has identified superconducting technology as a key enabler to deliver this airframe. Superconductors need to be cooled to cryogenic temperatures for normal operation. Using a sensitivity matrix, it was found that the Exchange Heat and Transport/Pump Cryogen functions are the most sensitive to input variation. The failure modes and effects analysis performed on the functional model show that the detection functions are critical during component failure. Quality Function Deployment (QFD) analysis shows the Exchange Heat and Transport/Pump Cryogen functions are also critical.
Keywords: Systems Engineering; Distributed Propulsion; Cryogenics